To Assess the Knowledge and Practices Regarding Postnatal Assessment of Women Among Nurses Working in Gynaecology Units of Selected Hospitals of District Ludhiana, Punjab: A Descriptive Study - Rachna Kapahi; Nidhi Sagar; Simrjeet Kaur; Mamta (International Journal of Midwifery Nursing And Practices, 2023)
This study was done to evaluate nurses' postnatal assessment of women's knowledge and practices. Postnatal assessment is a vital part of postnatal care in the fourth stage of labor for the women as it confirms the mother’s recovery from the effects of pregnancy, labor, and delivery. It provides an opportunity for the nurses to prevent many life-threatening complications and promote health status during this period. A descriptive research design was used with a convenience sampling technique on 60 nurses working in gynecology units of selected hospitals of district Ludhiana, Punjab. A systematic questionnaire and checklist for postnatal evaluation practice were used to gather data. Both descriptive and inferential statistics were used in the analysis. It was found that a maximum of nurses belonged to age-group of 20-29 years (mean age 29.31±7.768 years), were married, less than half of them were GNM, had experience of 1-2 years, worked in private hospitals regularly and most of them had never attended in-service education regarding postnatal assessment. Nearly half of the nurses (48.3%) had an average level of knowledge and most of the nurses (71.7%) had an average level of practice regarding the postnatal assessment of women. The association of the knowledge with practices regarding postnatal assessment of women among nurses was found to be highly significant (p<0.001) with a weak positive correlation (r=0.318, p=0.013). There was also a statistically significant association between experience, working institution, and type of employment with knowledge (p<0.05), and also found a significant association between working institution and practices (p<0.0). The study concluded that there was an average level of knowledge and practices regarding postnatal assessment and there was a positive effect of knowledge on practices regarding postnatal assessment of women among nurses.
Keywords: Knowledge; Postnatal assessment; nurses; practices